Duties and Powers of The Department of Public Works and Spatial Planning in The Implementation of Road in Kendal - Nabella Maharani Novanta (Jurnal Daulat Hukum, 2018)
This study discusses the role of the Department of Public Works and Spatial Planning in the implementation of the road in Kendal. Here is more towards the implementation of the supervision. Research problems concerning form of oversight, relations with relevant institutions, as well as the obstacles faced by the Department of Public Works and Spatial in Kendal. To answer these problems required legal research activities, using empirical juridical approach. Sources of data obtained through interviews with sources as well as legislation, legal theory, and the opinions of the leading scholars as support material, and then analyze it in order to get an answer scientifically.Keywords: Local Government; Roads Implementation; Monitoring.